#TITLE_ALTERNATIVE# - ANSORI (NIM : 10206069); Pembimbing : Prof. Dr. Eng. Zaki Su’ud, AZMY
A single channel thermal-hydraulic analysis is a form of analysis that discusses about the thermal energy transfer processes that occur within a coolant channel. In the case of PWR’s (Pressurized Water Reactor) cooling system we use water as the coolant. Water is used as a neutron moderator and as a medium of thermal energy transfer that produced by nuclear reactions that happen in the fuel. This coolant will flow in a closed loop that will heat the water on the other loop with a specific mass flow rate. In this process the mass flow rate will affect the rises of coolant temperature and also the pressure drop that occurs in the reactor. Under conditions of a particular mass flow rate, water will be able to experience a phenomenon that called Natural Circulation, in which water can flow naturally without the aid of mechanical energy from the outside. This phenomenon can be used as a form of security system when an reactor accident is happened, where the pump in the coolant loop can not be used, this study had obtained that at mass flow rate 285,8 gr/s coolant will reach natural circulation.